SUMO represses transcriptional activity of the Drosophila SoxNeuro and human Sox3 central nervous system-specific transcription factors. - Savare, J.; Bonneaud, N.; Girard, F. (Molecular Biology of the Cell, 2005)
Sry high mobility group (HMG) box (Sox) transcription factors are involved in the development of central nervous system (CNS) in all metazoans. Little is known on the molecular mechanisms that regulate their transcriptional activity. Covalent posttranslational modification by small ubiquitin-like modifier (SUMO) regulates several nuclear events, including the transcriptional activity of transcription factors. Here, we demonstrate that SoxNeuro, an HMG box-containing transcription factor involved in neuroblast formation in Drosophila, is a substrate for SUMO modification. SUMOylation assays in HeLa cells and Drosophila S2 cells reveal that lysine 439 is the major SUMO acceptor site. The sequence in SoxNeuro targeted for SUMOylation, IKSE, is part of a small inhibitory domain, able to repress in cis the activity of two adjacent transcriptional activation domains. Our data show that SUMO modification represses SoxNeuro transcriptional activity in transfected cells. Overexpression in Drosophila embryos of a SoxN form that cannot be targeted for SUMOylation strongly impairs the development of the CNS, suggesting that SUMO modification of SoxN is crucial for regulating its activity in vivo. Finally, we present evidence that SUMO modification of group B1 Sox factors was conserved during evolution, because Sox3, the human counterpart of SoxN, is also negatively regulated through SUMO modification.